Dental handpieces & accessories Part 1. Dental handpieces Sec. 1.2 Specification for straight & geared angle handpieces (BSI, 1992)
Dental handpieces, Dental instruments, Dental equipment, Dentistry, Design, Chucks, Mandrels, Temperature rise, Sterilization (hygiene), Torque, Force, Testing conditions, Test equipment, Dimensional tolerances, Dimensional measurement, Mechanical testing, Flow rates, Flow measurement, Cooling systems, Marking, Instructions for use